2020
DOI: 10.3390/ani10081321
|View full text |Cite
|
Sign up to set email alerts
|

Social Experience of Captive Livingstone’s Fruit Bats (Pteropus livingstonii)

Abstract: Social network analysis has been highlighted as a powerful tool to enhance the evidence-based management of captive-housed species through its ability to quantify the social experience of individuals. We apply this technique to explore the social structure and social roles of 50 Livingstone’s fruit bats (Pteropus livingstonii) housed at Jersey Zoo, Channel Islands, through the observation of associative, affiliative, and aggressive interactions over two data collection periods. We implement binomial mixture mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…Resource defense generally functions to provide a dominant individual with an adequate supply of some critical resource (often food) at the expense of less dominant individuals (usually conspecifics; [ 16 , 44 ] who are forced to move more often to acquire undefended foraging resources [ 16 , 28 ]. Although not directly tested in our study, in many territorial species, dominance is linked to body size [ 21 , 22 , 38 , 52 , 87 ], and the observed body size-dependent foraging movements of P. natalis are consistent with those of other nectivorous animals, including bats, that actively defend foraging resources [ 44 , 46 ].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Resource defense generally functions to provide a dominant individual with an adequate supply of some critical resource (often food) at the expense of less dominant individuals (usually conspecifics; [ 16 , 44 ] who are forced to move more often to acquire undefended foraging resources [ 16 , 28 ]. Although not directly tested in our study, in many territorial species, dominance is linked to body size [ 21 , 22 , 38 , 52 , 87 ], and the observed body size-dependent foraging movements of P. natalis are consistent with those of other nectivorous animals, including bats, that actively defend foraging resources [ 44 , 46 ].…”
Section: Discussionsupporting
confidence: 59%
“…While anecdotal observations suggest that smaller flying-fox individuals can be displaced from foraging sites by larger, dominant individuals (e.g., [ 53 ], to our knowledge, no studies of free ranging populations have directly tested whether foraging resource defense is body size-dependent in this taxon. This is likely due to the difficulty of observing individuals of known body mass interacting at foraging sites; however, diet and behavioral studies on captive populations of P. livingstonii demonstrated that older individuals [ 22 ], were more dominant and defended and/or displace smaller individuals from foraging resources [ 52 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal Observer was designed by Damien Caillaud and his team from the Dian Fossey Gorilla Fund International and first released in 2012. The application has been used to collect behavioral data in, for example, primates (Harrison et al, 2020;Schrock et al, 2019), humans (Dai et al, 2020), bats (Welch et al, 2020), and birds (van der Marel, Prasher, et al, 2020). The main sampling methods included in Animal Observer are focal animal and scan sampling.…”
Section: Animal Observermentioning
confidence: 99%
“…One of the most attractive features of SNA is that it allows to study the social organisation of animals at all levels (individual, dyad, group, population) and for all types of interaction (e.g., aggressive, cooperative, sexual, Krause et al, 2009), allowing a plethora of novel insights into the evolution and maintenance of sociality to be elucidated (Wey et al, 2008;Pinter-Wollman et al, 2014;Krause et al, 2015;Webber and Vander Wal 2019;Sosa et al, 2021b). As social structure can also affect population growth rates, dispersal and gene flow, network analysis also has the potential to be an important tool in the management of wild populations (Tarlow & Blumstein, 2007;Schakner et al, 2017, Snijders et al, 2017, Welch et al, 2020.…”
Section: Introductionmentioning
confidence: 99%